2019
DOI: 10.1111/bjh.16315
|View full text |Cite
|
Sign up to set email alerts
|

Platelet biology of the rapidly failing lung

Abstract: Summary Acute respiratory distress syndrome (ARDS) is characterized by a rapid‐onset respiratory failure with a mortality rate of approximately 40%. This physiologic inflammatory process is mediated by disruption of the alveolar‐vascular interface, leading to pulmonary oedema and impaired oxygen exchange, which often warrants mechanical ventilation to increase survival in the acute setting. One of the least understood aspects of ARDS is the role of the platelets in this process. Platelets, which protect vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 125 publications
0
29
0
1
Order By: Relevance
“…Megakaryocytes (MKs) are normally present in the human lung and play a role in platelet homeostasis [1,2]. Originally described by Aschoff in 1893, the interest in pulmonary MKs and their platelet production has raised considerably during the last decade [1][2][3]. Several studies have shown that platelets participate in lung damage, particularly in acute lung injury [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Megakaryocytes (MKs) are normally present in the human lung and play a role in platelet homeostasis [1,2]. Originally described by Aschoff in 1893, the interest in pulmonary MKs and their platelet production has raised considerably during the last decade [1][2][3]. Several studies have shown that platelets participate in lung damage, particularly in acute lung injury [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that platelets act as important mediators of innate defenses: platelet adhesion, activation, and degranulation are the essential steps in this process, in which platelet-associated surface receptor molecules play a pivotal role in the development of inflammation ( 148 ).…”
Section: Aβ Is a Vital Defense Protein With Multiple Rolesmentioning
confidence: 99%
“…Originally described by Aschoff in 1893, the interest in pulmonary MKs and their platelet production has raised considerably during the last decade [1][2][3]. Several studies have shown that platelets participate in lung damage, particularly in acute lung injury [2,3]. MKs are usually not mentioned as a characteristic histopathologic nding associated to acute pulmonary injury [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In ammatory injury to alveolar epithelium and endothelial cells, resulting in intra-alveolar edema, deposition of brin and formation of microthrombi are important pathogenic mechanisms of DAD. There is experimental and clinical evidence that platelets contribute to alveolar damage and repair in acute respiratory distress syndrome (ARDS) and other forms of acute lung injury [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation